Lipocalin-2 and neutrophil activation in pancreatic cancer cachexia - Deng, Min; Aberle, Merel R.; van Bijnen, Annemarie A. J. H. M.; van der Kroft, Gregory; Lenaerts, Kaatje; Neumann, Ulf P.; Wiltberger, Georg; Schaap, Frank G.; Olde Damink, Steven W. M.; Rensen, Sander S. (Frontiers in Immunology, 2023)
Background: Cancer cachexia is a multifactorial syndrome characterized by body weight loss and systemic inflammation. The characterization of the inflammatory response in patients with cachexia is still limited. Lipocalin-2, a protein abundant in neutrophils, has recently been implicated in appetite suppression in preclinical models of pancreatic cancer cachexia. We hypothesized that lipocalin-2 levels could be associated with neutrophil activation and nutritional status of pancreatic ductal adenocarcinoma (PDAC) patients. Methods: Plasma levels of neutrophil activation markers calprotectin, myeloperoxidase, elastase, and bactericidal/permeability-increasing protein (BPI) were compared between non-cachectic PDAC patients (n=13) and cachectic PDAC patients with high (≥26.9 ng/mL, n=34) or low (<26.9 ng/mL, n=34) circulating lipocalin-2 levels. Patients’ nutritional status was assessed by the patient-generated subjective global assessment (PG-SGA) and through body composition analysis using CT-scan slices at the L3 level. Results: Circulating lipocalin-2 levels did not differ between cachectic and non-cachectic PDAC patients (median 26.7 (IQR 19.7-34.8) vs. 24.8 (16.6-29.4) ng/mL, p=0.141). Cachectic patients with high systemic lipocalin-2 levels had higher concentrations of calprotectin, myeloperoxidase, and elastase than non-cachectic patients or cachectic patients with low lipocalin-2 levels (calprotectin: 542.3 (355.8-724.9) vs. 457.5 (213.3-606.9), p=0.448 vs. 366.5 (294.5-478.5) ng/mL, p=0.009; myeloperoxidase: 30.3 (22.1-37.9) vs. 16.3 (12.0-27.5), p=0.021 vs. 20.2 (15.0-29.2) ng/mL, p=0.011; elastase: 137.1 (90.8-253.2) vs. 97.2 (28.8-215.7), p=0.410 vs. 95.0 (72.2-113.6) ng/mL, p=0.006; respectively). The CRP/albumin ratio was also higher in cachectic patients with high lipocalin-2 levels (2.3 (1.3-6.0) as compared to non-cachectic patients (1.0 (0.7-4.2), p=0.041). Lipocalin-2 concentrations correlated with those of calprotectin (rs=0.36, p<0.001), myeloperoxidase (rs=0.48, p<0.001), elastase (rs=0.50, p<0.001), and BPI (rs=0.22, p=0.048). Whereas no significant correlations with weight loss, BMI, or L3 skeletal muscle index were observed, lipocalin-2 concentrations were associated with subcutaneous adipose tissue index (rs=-0.25, p=0.034). Moreover, lipocalin-2 tended to be elevated in severely malnourished patients compared with well-nourished patients (27.2 (20.3-37.2) vs. 19.9 (13.4-26.4) ng/mL, p=0.058). Conclusions: These data suggest that lipocalin-2 levels are associated with neutrophil activation in patients with pancreatic cancer cachexia and that it may contribute to their poor nutritional status.